‘보람찬/Pecos’ 재조합 자식 집단을 이용한 수량 및 입형 관련 형질 양적형질 유전자좌 분석 - 박현수(Hyun-Su Park), 이창민(Chang-Min Lee), 서정환(Jeonghwan Seo), 박송희(Songhee Park), 이건미(Keon-Mi Lee), 박재령(Jae-Ryoung Park), 정오영(O-Young Jeong) (Korean journal of breeding, 2025)
‘Boramchan’ is a high-yielding, mid-late maturing temperate japonica rice cultivar developed in Korea, while ‘Pecos’ is an early-maturing tropical japonica cultivar from the United States with medium-grain shape characteristics. In this study, quantitative trait loci (QTL) analysis was conducted on yield- and grain-related traits using recombinant inbred lines derived from a cross between ‘Boramchan’ and ‘Pecos’ in order to broaden the genetic diversity of these traits in Korean japonica rice varieties. QTLs for heading date were identified on chromosomes 3 and 6, with Hd6 and Hd1 proposed as candidate genes for this trait. The major heading date gene Hd1 exhibited pleiotropic effects, influencing not only the heading date (HD) but also multiple yield components, including culm length, panicle length, number of spikelets per panicle (NS), 1,000-grain weight (TGW), ratio of ripened grain (RRG), brown/rough rice ratio, and grain yield per plant. The minor heading date gene Hd6 showed a masking effect on HD and NS, depending on the allele type of Hd1. Allelic combinations of Hd1 and Hd6 allowed HD regulation for approximately 30 days. As more functional alleles associated with delayed heading accumulated, the values of yield-related traits gradually increased. Three QTLs for grain-related traits–qGL2, GW5, and qGS10–were identified on chromosomes 2, 5, and 10, respectively. GW5 was confirmed as a major gene with significant effects on phenotypic variation, influencing all grain-related traits, including grain length (GL), width (GW), thickness (GT), length to width ratio, and TGW. qGL2 was associated with GL and colocalized with qNS2, a QTL related to NS. qGS10 was identified as a QTL that affected GW, GT, and TGW. Allelic combinations of qGL2, GW5, and qGS10 influenced not only grain-related traits but also variation in yield-related traits. Combinations carrying the gw5- allele from ‘Boramchan’ generally exhibited favorable characteristics in terms of yield potential. Furthermore, the introduction of qGL2P and qGS10P alleles from ‘Pecos’ contributed to the diversification of grain shape and showed positive effects on NS, RRG, and yield. Novel allele combinations, such as qGL2P-gw5--qGS10B and qGL2P-gw5--qGS10P are expected to enhance the genetic diversity of yield- and grain-related traits in Korean japonica rice varieties. KCI Citation Count: 0